2011
DOI: 10.2215/cjn.07810910
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease Progression and Outcome According to Serum Phosphorus in Mild-to-Moderate Kidney Dysfunction

Abstract: SummaryBackground and objectives Several factors might alter serum phosphate homeostasis and induce hyperhosphatemia in patients with chronic kidney disease (CKD) not requiring dialysis. However, whether and to what extent hyperphosphatemia is associated with a poor prognosis in different CKD patient groups remain to be elucidated.Design, setting, participants & measurements We utilized the "Prevenzione Insufficienza Renale Progressiva" (PIRP) database, a large project sponsored by the Emilia-Romagna Health In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
4
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(101 citation statements)
references
References 33 publications
4
90
4
3
Order By: Relevance
“…The association between hyperphosphatemia and lower age is now well recognized, as it has been shown in several previous studies in different settings: in the community setting, this association was found in a general population [19], a diabetic population [20], and a CKD population [21]; in the hospital setting, the association was shown in vascular patients scheduled for major surgery [22] and also in a dialysis population [9,10]. Various mechanisms may explain this association, including increased undernutrition with age, decreased renal phosphate reabsorption, and hormonal factors.…”
Section: Discussionmentioning
confidence: 60%
“…The association between hyperphosphatemia and lower age is now well recognized, as it has been shown in several previous studies in different settings: in the community setting, this association was found in a general population [19], a diabetic population [20], and a CKD population [21]; in the hospital setting, the association was shown in vascular patients scheduled for major surgery [22] and also in a dialysis population [9,10]. Various mechanisms may explain this association, including increased undernutrition with age, decreased renal phosphate reabsorption, and hormonal factors.…”
Section: Discussionmentioning
confidence: 60%
“…These findings have been corroborated independently in other countries. For example, an Italian group showed an association between serum phosphorus and the likelihood of death in >1700 CKD patients (13). A recent meta-analysis including 47 studies and 327,644 CKD participants further supports the evidence of an association between higher serum phosphorus and mortality in this population (14).…”
Section: Association Between Serum Phosphorus and Cvdmentioning
confidence: 89%
“…Clinical evidence demonstrates that hyperphosphatemia is associated with an adverse effect on renal or cardiovascular function and an increased mortality risk, independent of other traditional risk factors. [3][4][5] The Kidney Disease Outcomes Quality Initiative (KDOQI) in the USA have recommended serum phosphorus targets of 3.5-5.5 mg/dL (1.13-1.78 mmol/L) in patients receiving dialysis. 6 Despite dietary restriction and adequate dialysis, the majority of dialysis patients suffering from hyperphosphatemia still need oral phosphate binders to control their phosphate levels and thereby reduce mortality.…”
Section: Introductionmentioning
confidence: 99%